Common Bile Duct Dilatations in Asymptomatic Neonates: Incidence and Prognosis - Shun-Feng Lin; Hung-Chang Lee; Chun-Yan Yeung; Chuen-Bin Jiang; Wai-Tao Chan (Gastroenterology Research and Practice)
Background. This retrospective study reviewed 213 asymptomatic neonates with common bile duct (CBD) dilatations diagnosed via ultrasound to evaluate their incidence and outcomes. Materials and Methods. From August 2001 to July 2010, 18,230 abdominal ultrasound scans were performed as newborn screening. There were 213 (1.17%) cases of CBD dilatation. Dilatation of neonatal CBD was defined when its diameter was ≥2 mm. The neonates’ birth history, CBD size, and follow-up results were analyzed. Results. In the 213 infants, four cystic dilatations (1.88%, 4/213) that were eventually diagnosed as choledochal cysts (CC). Among 209 neonates with fusiform dilatations (size 2.0–6.7 mm), 77 had ultrasound follow-up and 87% of them resolved spontaneously which were diagnosed as transient CBD dilatation (TCBDD). Eighty percent of TCBDDs resolved within 6 months. Patients with initial CBD size ≥3 mm had significantly lower resolution rate and neonates whose mothers are older than 35 years took longer time to resolve. Conclusion. The incidence of CBD dilatation in asymptomatic neonates was 1.17%. Eighty percent of TCBDDs resolved within 6 months. Regular ultrasound follow-up every 6 months may be appropriate for asymptomatic neonates with fusiform CBD dilatations to ensure resolution or progression.